A Clear-Sighted Witness: Trauma and Memory in Maryse Condé's Desirada - Dawn Fulton (Studies in 20th & 21st Century Literature, 2005)
Maryse Condé's 1997 novel recounts a young Guadeloupean woman's frustrating search for the identity of her father. Because the information she seeks is initially guarded by her mother and later contradicted by friends and family, this heroine confronts an epistemological impasse, a potentially traumatic event to which she will never have direct access. Informed by Toni Morrison's reflections on memory and invention and by recent studies in trauma theory, this essay examines the ways in which Condé negotiates this impasse in her novel, creating a narrative field of knowledge that allows for its own lacunae and maintains multiple registers of experience. I propose that while the protagonist's creative endeavor is ultimately an optimistic one in that she is able to forge a less restricted notion of her own identity, the isolation brought by her personal crisis nonetheless cautions the reader against interpreting this individual search for identity on a collective scale. With this particular modulation of the traditional Caribbean identity quest novel, Condé suggests that collective memory may be fragmented not only because of traumatic events, but also, and perhaps more irreparably, along the faultliness of temporal, spatial, and interpretive divides.
Keywords: Maryse Condé; Guadeloupean woman; Guadeloupean; traumatic event; trauma; Toni Morrison; memory; invention; trauma theory; lacunae; father-daughter relationship; mother-daughter relationship; father; daughter; mother; family; friends; identity; isolation; personal crisis; Caribbean identity; collective memory; temporal; spatial